Clinical, electrocardiographic, and electrophysiological characteristics of left upper septal fascicular ventricular tachycardia. Issue 4 (4th February 2017) - Guo, Xiao-Gang; Liu, Xu; Zhou, Gong-Bu; Sun, Qi; Yang, Jian-Du; Luo, Bin; Ouyang, Feifan; Ma, Jian; Zhang, Shu
Abstract: Aims: We sought to investigate the clinical, electrocardiographic, and electrophysiological characteristics of left upper septal fascicular ventricular tachycardia (LUS-VT). Methods and results: Eleven consecutive patients with LUS-VT were identified among 196 patients with left fascicular ventricular tachycardia (VT). Clinical VTs presented as paroxysmal in 8 patients and incessant in 3 patients. Six patients had previous left posterior fascicular VT ablation history. All VTs had narrow QRS complexes with QRS duration of 101.1 ± 9.2 ms. The frontal QRS axis was normal or right deviation. Precordial morphology was either right bundle branch block type or similar to that of sinus rhythm. A retrograde His with H-V interval of 21.9 ± 7.2 ms was recorded during VT. The earliest Purkinje potential (PP) to QRS interval during VT averaged 35.7 ± 4.5 ms. Clear diastolic potentials (DPs) with high frequency and low amplitude were found in only one patient. Ten patients were managed successfully by 11 ablation sessions, and 1 patient declined ablation. Successful targets at the left upper septum were sites with the earliest PP (9 cases) or with DP (1 case) during VT. After ablation, 2 cases (10%) developed new left anterior hemiblock or incomplete left bundle branch block. No VT recurred during a median follow-up period of 3.2 (range 1.0–12.7) years. Conclusion: LUS-VT presented as narrow QRS complex tachycardia. Some LUS-VTs occurred after ablation targeting left posterior fascicular VT. The VTs can be managed successfully by focal ablation at the left upper septum with a mild risk of fascicular injury.